2023
DOI: 10.1097/md.0000000000036081
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam-based anesthesia with flumazenil allows faster emergence than propofol-based anesthesia in older patients undergoing spinal surgery: A randomized controlled trial

Yukari Toyota,
Takashi Kondo,
Kyoko Oshita
et al.

Abstract: Background: Remimazolam is a novel, ultrashort-acting benzodiazepine that can be antagonized by flumazenil. This study aimed to determine whether remimazolam-based anesthesia with flumazenil provides a more rapid emergence than propofol-based anesthesia in older patients undergoing spinal surgery. Methods: This was a prospective, single-blind, randomized controlled trial. Forty-four patients > 75 years old who had undergone spinal surgery were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Remimazolam is a reversal agent, flumazenil [13]. Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Remimazolam is a reversal agent, flumazenil [13]. Previous studies on remimazolam have reported that when flumazenil is administered postoperatively, the emergence time is shorter than that with traditional anesthetic drugs [41][42][43]. In the absence of flumazenil, the emergence time was not different or longer [44,45].…”
Section: Discussionmentioning
confidence: 99%